Diversity and Abundance of Phytoplankton in Coastal Areas in Kendari Southeast Sulawesi Indonesia - Indrayani, Indrayani; Haslianti, Haslianti; Asmariani, Asmariani; Ardiansyah, Ardiansyah (Journal of Agroscience Indonesia, 2023)
Phytoplankton is a microscopic algae that can be found in almost all aquatic habitats. Phytoplankton have an important ecological role in the waters, as the basis of the food chain and as a producer of oxygen, where their composition and abundance are strongly influenced by various environmental factors. This study aims to determine the community structure of phytoplankton including the diversity, abundance and dominance of phytoplankton found in various locations in coastal waters in Southeast Sulawesi. Sampling was carried out in several coastal waters in Southeast Sulawesi including Nambo, Bokori, Batu Gong, Toronipa and Tanjung Tiram beaches. Plankton sampling was carried out by filtering about 100 L of seawater using a plankton net with a mesh size of 20 µm. The filtered plankton samples were then preserved in 4% formalin for further observation in the laboratory. Water quality measurements of temperature, salinity, brightness and pH were carried out in situ while nitrate, phosphate and ammonia were carried out ex-situ. The results showed that there were about 30 species of phytoplankton found where the most species were found in Bokori Island (22 species) followed by Tanjung Tiram beach (21 species), Toronipa beach (19 species) and both Nambo and Batu Gong beaches with 17 species. The highest abundance of phytoplankton was found on Bokori Island (563 individuals/L) and the lowest abundance was found on Batu Gong beach (237 individuals/L). The highest diversity index value was found at Toronipa Beach (2.72) while the lowest diversity index value was found at Batu Gong Beach (2.13). For the dominance index value, the highest value was obtained at Batu Gong Beach (0.18) and the lowest value was obtained at Toronipa Beach (0.08). The difference in the structure of the phytoplankton community found in different locations is due to variation of the environmental conditions.